A Study of Training Preferences in Rice Cultivation in Jammu District of J&K State - Yogesh Kumar and M. S. Nain, (Indian Journal of Extension Education, 2013)
Ever increasing population poses production needs of 140 million tonnes of rice per year by 2025 requiring highermanagement practices. This demands increased emphasis on need based training of farmers in rice productiontechnology. The present study was undertaken in Jammu district of J&K state to delineate the farmers' training need in riceproduction. The study was conducted on 80 randomly selected farmers of R.S. Pura block with a pre-structured interviewschedule. The findings revealed that the farmers were requiring training in almost all the subject matter areas of riceproduction specially use of insecticides, pesticides, use of manures and fertilizers, seed and seed technology and watermanagement.